Analysis of Temperature Sensors That Transmit Data in Automation Systems - Oripov Shoxruxmirzo Muzaffarbek O’g’li; Valiyev Durbek Xayotbek O’g’li (Zien Journals, 2022)
This article describes the properties and applications of temperature sensors. Analysis of different types of temperature sensors from the most common sensors.
Keywords: Thermistors; Temperature; Sensors; Resistance